The Historiography of the Holocaust
XI, 573 p.
Keywords: This collection of essays by leading scholars in their fields provides the most comprehensive and up-to-date survey of Holocaust historiography available. Covering both long-established historical disputes as well as research questions and methodologies that have developed in the last decade's massive growth in Holocaust Studies, this collection will be of enormous benefit to students and scholars alike.